2017
DOI: 10.1371/journal.pone.0174601
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes of hypoglycemia in patients with advanced diabetic kidney disease on dialysis: A national cohort study

Abstract: BackgroundPatients with advanced diabetic kidney disease (DKD) behave differently to diabetic patients without kidney disease. We aimed to investigate the associations of hypoglycemia and outcomes after initiation of dialysis in patients with advanced DKD on dialysis.MethodsUsing National Health Insurance Research Database, 20,845 advanced DKD patients beginning long-term dialysis between 2002 and 2006 were enrolled. We investigated the incidence of severe hypoglycemia episodes before initiation of dialysis. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 45 publications
0
34
1
Order By: Relevance
“…Diabetic nephropathy (DN) is a serious and common chronic microvascular complication of DM [ 2 ], that is the main cause of mortality in patients with diabetes, as well as a major contributor to the high prevalence of end-stage renal disease (ESRD) worldwide [ 3 ]. The global prevalence of DM is growing rapidly, especially in developing countries, and the incidence rates of both DN and ESRD continue to increase [ 4 ]. Hyperglycemia is accompanied by an accelerated rate of formation of advanced glycation end products (AGEs).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is a serious and common chronic microvascular complication of DM [ 2 ], that is the main cause of mortality in patients with diabetes, as well as a major contributor to the high prevalence of end-stage renal disease (ESRD) worldwide [ 3 ]. The global prevalence of DM is growing rapidly, especially in developing countries, and the incidence rates of both DN and ESRD continue to increase [ 4 ]. Hyperglycemia is accompanied by an accelerated rate of formation of advanced glycation end products (AGEs).…”
Section: Introductionmentioning
confidence: 99%
“…DKD is one of the most important microvascular complications of diabetes, and its prevalence has increased dramatically worldwide in the past few decades [3,4]. It has been reported that DKD accounts for approximately 20% of new dialysis prescriptions [5], and the high medical cost of renal dialysis treatment has created an urgent need for additional therapeutic strategies for DKD [6]. Comprehensive measures such as hypoglycemic and antihypertensive treatments have demonstrated bene cial effects in preventing the development of DKD, especially when used at the stage of microalbuminuria, and angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor II blockers (ARBs) reduce the risk of progression of DKD [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with these agents is complicated by the fact that renal disease is an independent risk factor for hypoglycemia through several mechanisms including decreased renal insulin clearance and reduced renal glucose production during counterregulation [ 21 23 ]. Furthermore, hypoglycemia is of particular concern in patients with advanced renal disease, as it leads to greater risk of declining renal function, stroke, and excessive mortality [ 22 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%